High-strength joint of nuclear-grade FeCrAl alloys achieved by friction stir welding and its strengthening mechanism. (May 2021) - Hu, Yanying; Zhao, Yunqiang; Peng, Yongbing; Yang, Weiqi; Ma, Xianfeng; Wang, Biao
Graphical abstract: Abstract: Nuclear-grade iron-chromium-aluminum (FeCrAl) alloys are promising candidates for accident tolerant fuel (ATF) cladding materials employed in advanced light-water reactors. Apart from the fusion welding processes, it is necessary to explore available solid-state joining processes such as Friction Stir Welding (FSW) for the FeCrAl alloys. In this study, the feasibility of friction stir welding in the achievement of high-strength Fe-13Cr-5Al alloy joint was investigated. The results demonstrated that a nuclear-grade FeCrAl alloy joint with nominal ultimate tensile strength of ∼629 MPa and fraction elongation of ∼19 % was successfully fabricated using friction stir welding (FSW). For the first time, the joint efficiency of FeCrAl alloys was approximately 100 % or better according to microhardness and tensile tests. Texture in the stir zone (SZ) consisted of a mixture of J ¯ 1 ¯ 1 ¯ 0 [ 1 ¯ 1 2 ¯ ], D 1 1 ¯ 1 ¯ 2 [ 111 ], D 2 1 ¯ 1 ¯ 2 [ 111 ], and E ¯ 1 ¯ 1 ¯ 0 [ 1 ¯ 11 ] components due to severe simple-shear strain. Microstructures in the SZ were predominately refined through discontinuous dynamic recrystallization (DDRX) due to the high-density of high-angle grain boundaries (HABs) and the abundancy of triple junctions induced by the increased strain. The excellent properties of the FeCrAl alloy joint were attributed to the formation of high-density low-angle boundaries (LABs) and refined grain structures. The fundamental discoveries in this study reveal a promising application prospect of FSW in the joining of nuclear reactor ATF cladding materials.